Strategi Pemasaran Produk Pembiayaan Murabahah Di BMT Buana Mas Arcawinangun pada Masa Pandemi Covid-19 - Lukman Maulana; Safitri Mukarromah (UM Purwokerto Press, 2022)
This study aims to examine the marketing strategy carried out by Baitul Maal Wat Tamwil (BMT) Buana Mas Arcawinangun. The type in this research is field research with a qualitative approach, while the data collection techniques are carried out by observation, interviews, and documentation. For data analysis, descriptive qualitative by describing various reports encountered during the research process. The results of this study indicate that the marketing strategy carried out by BMT Buana Mas Arcawinangun has four strategies, namely the strategy of picking up the ball, targeting Funding Officers, holding a Healthy Walk Event Once a Month (Distributing Brochures), and visiting the Majlis Taklim Association or Recitation. While the application of marketing for murabahah financing products generally adheres to the 4P marketing mix theory, the marketing mix consists of 4Ps, namely: production (product components can be in the form of variety, quality, design, packaging, and form of service), price (price components can be in the form of price quotes, discounts, payment terms, and credit terms), location (location components can be distribution channels), location, inventory, transportation, and logistics) and promotions (promotion components can include advertising, personnel sales, public relations, direct selling, and promotions).